Risk factors for malnutrition among hospitalized gastroenterological patients - Roganović, Branka; Perić, Saša; Petrović, Stanko; Roganović Sarić, Ana; Roganović, Andrija (Vojnosanitetski pregled, 2022)
Background/Aim. Risk factors for malnutrition of patients during hospitalization have not been precisely determined. The aim of the study was to determine these factors in hospitalized gastroenterological patients. Methods. Nutritional status (NS) of 650 gastroenterological patients was assessed at the hospital admission and at discharge by the six parameters: unintentional weight loss, lymphocyte count, serum albumin concentration, body mass index, triceps skinfold thickness, and mid-upper arm muscle circumference. The influence on NS at discharge was tested for ten factors: gender, age, affected organ, the nature, severity, and complications of the disease, the length of hospitalization, mobility worsening during hospitalization, Karnofsky score, and NS on admission. Primary and secondary risk factors were defined among the factors significantly influencing malnutrition. Results. Seven factors were found to be the independent predictors for malnutrition in hospitalized gastroenterological patients. NS at admission was considered as a primary risk factor (Forward: Wald multivariate logistic regression analysis, p < 0.001 for five applied assessment parameters). The other six factors, obtained in the evaluation according to 1-3 assessment parameters, were considered as secondary risk factors: severe disease activity, malignancy, the existence of complications, male gender, hospitalization > 14 days, and mobility worsening during the hospitalization (Forward: Wald multivariate logistic regression analysis, p from 0.001 to 0.027). Conclusion. There are seven risk factors for malnutrition among gastroenterological patients during hospitalization. Timely nutritional support in these patients can prevent the development of intrahospital malnutrition and its negative influence on the clinical outcome.
Keywords: gastrointestinal diseases; hospitalization; malnutrition; nutritional status; risk factors; treatment outcome